Memahami Hadis-Hadis Misoginis dengan Pendekatan Spirit Ayat-Ayat Al-Qur’an - Mira Fauziah (El-Sunan: Journal of Hadith and Religious Studies, 2023)
A refreshment of the understanding of misogynistic hadiths is absolutely necessary. The reason is not primarily to align with the demands of modern intellectual development, but rather to free the understanding from gender prejudices. As modern Islamic thinkers have demonstrated, the hadiths in question do not actually emphasize superiority or inferiority based on gender, which in classical interpretations have been embellished with explanations and additions that marginalize women. Consequently, the understanding of these hadiths merely accommodates the socio-historical facts that have sidelined women's rights. This interpretation of hadiths becomes a powerful religious tool for disempowering women. This phenomenon is clearly a contradiction. On one hand, the Qur'an strongly emphasizes the values of justice, equality, and freedom. But on the other, the understanding of hadiths has obstructed these fundamental values. ABSTRAK Penyegaran pemahaman terhadap hadis-hadis misoginis mutlak dilakukan. Alasannya bukan terutama untuk menyesuaikan dengan tuntutan perkembangan dunia pemikiran modern, melainkan untuk membebaskan pemahaman dari prasangka jender. Seperti telah ditunjukkan oleh para pemikir Islam modern, hadis-hadis yang sebenarnya tidak menekankan superioritas inferioritas atas dasar jenis kelamin yang dalam tafsir klasik telah dibumbui penjelasan dan tambahan yang memarjinalisasikan perempuan. Sehingga, pemahaman hadis bersifat semata-mata mengakomodasi fakta sosiologis-historis yang telah menyingkirkan hak-hak perempuan. Pemahaman hadis menjadi alat religius sangat ampuh untuk tidak memberdayakan perempuan. Fenomena ini jelas merupakan sebuah kontradiksi. Di satu sisi al-Qur`an sangat menekankan nilai-nilai keadilan, persamaan dan kebebasan. Tetapi di sisi lain, pemahaman terhadap hadis telah menghalangi nilai-nilai utama itu.